Radosława Piwowarskiego podróże nostalgiczne. Kreowanie pamięci wspólnotowej i „realizm pamięci” w narracjach o Dolinie Dzieciństwa i Młodości - Marczak, Mariola (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article comprises a study of the creative work of the Polish director Radosław Piwowarski, represented by his most characteristic films. The author points out the merger of stylized realism and of the nostalgic (or to be more precise – the realism stylized by means of nostalgia) as constitutive for the film style of this film artist. As a result of film analyses, the narrative structures of Piwowarski’s films appear to be memory structures, as they re-create the reality remembered by the filmmaker, who usually chooses the topos of a trip down memory lane to express his personal and subjective point of view. The film’s story becomes the image of the subjective reality, since it is a product of personal memory, consciousness and imagination. Piwowarski refers to the motif of the Valley of Childhood and Youth, vivid and active in the Polish literature and cinema, as an universum closed up in the past and lost forever, which, however, is accessible through the activity of recalling. The director, by the act of re-creation of a world personally remembered, actualizes the collective memory and therefore creates a community of memory with viewers of his films. The screen image of the past reality therefore gains double reliability – as a personal confession and as a record of the past; in consequence, we achieve the esthetical category of realism of memory.